2020
DOI: 10.1007/s10637-020-01001-5
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 study of crenigacestat (LY3039478), the Notch inhibitor, in Japanese patients with advanced solid tumors

Abstract: Summary Background This phase 1, single-center, nonrandomized, single-arm, open-label, dose-escalation study, evaluated the tolerability of crenigacestat, a γ-secretase inhibitor as an oral Notch inhibitor in Japanese patients with advanced solid tumors. Methods The study consisted of 2 dose levels of crenigacestat (25 mg and 50 mg), administered orally 3 times per week (TIW) over a 28-day cycle until disease progression, development of unacceptable toxicity, or any other discontinuation criteria were met. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Importantly, unlike DAPT, LY3039478 is an orally bioavailable selective Notch inhibitor that has already been administered in a phase 1 clinical trial for solid tumor treatment. [44][45][46][47] Consequently, LY3039478 is likely to be safer and closer to clinical translational use in NASH patients. Nevertheless, pharmacological Notch inhibitors such as DAPT and LY3039478 are likely to affect not only LSECs but also hepatocytes, Kupffer cells, and even HSCs, highlighting the need for the identification or development of EC-specific Notch inhibitors as potential NASH treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, unlike DAPT, LY3039478 is an orally bioavailable selective Notch inhibitor that has already been administered in a phase 1 clinical trial for solid tumor treatment. [44][45][46][47] Consequently, LY3039478 is likely to be safer and closer to clinical translational use in NASH patients. Nevertheless, pharmacological Notch inhibitors such as DAPT and LY3039478 are likely to affect not only LSECs but also hepatocytes, Kupffer cells, and even HSCs, highlighting the need for the identification or development of EC-specific Notch inhibitors as potential NASH treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…A phase III comparative study (study 305) reported that eribulin improved OS of patients with previously treated metastatic breast cancer compared with TPC [ 15 ]. In Japan, an observational study concluded that eribulin may be a first-line treatment candidate for patients with HER2-negative advanced breast cancer [ 16 ]. The real-world observational ESME program enrolling 16,703 metastatic breast cancer patients evaluated outcomes of patients treated with eribulin as second-, third- and fourth-line treatment and found a significant improvement in OS and PFS compared with other chemotherapies for all lines among the HER2-negative patient subgroup [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 patients had stable disease. The most common toxicities included: fatigue (82%; grade 36%), mucositis, (71%;), neutropenia (59%), anemia (59%), and hypertriglyceridemia (59%) NCT01218620; I Adult solid neoplasm 2010; Completed; USA Unpublished LY3039478 γ-secretase inhibitor NCT02836600 [ 56 ]; I Advanced solid tumor 2016; Active, not recruiting; Japan In 11 enrolled Japanese patients, no dose-limiting toxicities or dose-limiting equivalent toxicities were observed. 1 patient (14.3%) with a desmoid tumor showed tumor size shrinkage of 22.4% and had stable disease for 22.5 months.…”
Section: Components Basic Function and Inhibition Of Notch Signalingmentioning
confidence: 99%